Multimedia security technologies for digital rights management (Elsevier, 2006)
A book of the utmost importance to practitioners working in the explosive field of securing multimedia technology applications.Security is a major concern in an increasingly multimedia-defined universe where the Internet serves as an indispensable resource for information and entertainment. Digital Rights Management (DRM) is the technology by which network systems protect and provide access to critical and time-sensitive copyrighted material and/or personal information. This book equips savvy technology professionals and their aspiring collegiate protégés with the latest technologies, strategies and methodologies needed to successfully thwart off those who thrive on security holes and weaknesses.